AUGMENTATIVE AND ALTERNATIVE COMMUNICATION IN THE SCHOOL CONTEXT: POTENTIALITIES, DILEMMAS, AND TEACHER MEDIATION IN THE INCLUSION OF A NONVERBAL AUTISTIC CHILD - Pozzobon, Lisiane Fagundes; Pozzobon, Oldair José; Pozzobon, Paola Fagundes; Marquezan, Lorena Inês Peterini; Antunes, Helenise Sangoi (Seven Editora, 2025)
This article describes the use of Augmentative and Alternative Communication (AAC) in Early Childhood Education, analyzing how teacher mediation and communicative planning influence the balance between technological support and encouragement of oral communication with a nonverbal autistic child. Methodologically, the study articulates a critical literature review with an experience report developed in 2024 in the educational care of a four-year-old child, using modeling, systematic observation, and analysis of communicative interactions. The results indicate that AAC expanded functional communication, reduced dysregulated behaviors, and favored participation in school routines. However, risks related to communicative convenience and the prioritization of the device in situations of greater cognitive demand were evident, limiting attempts at vocalization. The study concludes that the effectiveness of AAC depends on teacher intentionality, monitoring of its use, and pragmatic diversification, offering recommendations for school practices and teacher training. When correctly mediated, AAC enhances inclusion and autonomy, thus preserving the protagonism of the attempt at verbalization.DOI: https://doi.org/10.56238/sevened2025.038-067